Evidence on the within-industry agglomeration of R&D, production, and administrative occupations - Benjamin Goldman; Thomas H. Klier; Thomas Walstrum (Federal Reserve Bank of Chicago, 2016)
To date, most empirical studies of industrial agglomeration rely on data where observations are assigned an industry code based on classification systems such as NAICS in North America and NACE in Europe. This study combines industry data with occupation data to show that there are important differences in the spatial patterns of occupation groups within the widely used industry definitions. We focus on workers in manufacturing industries, whose occupations almost always fit into three groups: production, administrative, or R&D. We then employ two approaches to document the spatial distributions of each group within an industry. First, we calculate the distribution of employment shares across local labor markets and second, we calculate a version of the Duranton and Overman (2005) agglomeration index. Both approaches reveal appreciable differences in the spatial distribution of occupation groups within most manufacturing industries. These differences have important implications for our understanding of the sources of industrial agglomeration, the spatial agglomeration of innovation, the effectiveness of local economic development initiatives, and the spatial properties of particular industries.
Keywords: 330